Gestión de mantenimiento en la mejora de métodos de trabajo para disminuir los costos de mantenimiento preventivo en una empresa cementera - Castillo Garcia, Omar Andre (2019)
The objective of this thesis is to reduce the costs of preventive maintenance in the cement industry by applying the improvement of work methods in maintenance management. A non-probabilistic sampling was carried out for convenience, having as a population the operations of mechanical preventive maintenance and as a shown the operations of preventive mechanical maintenance in the Sections of 467, C67, CT6 and CT7 (Milling); CG1 (Coal) and EM6 (Embalming). The research method is deductive and the design of the research is pre-experimental with test and post-test. The technique of data collection was observation and data obtained with time study formats were recorded. The annual time of the observed maintenance was reduced, from a total of 645.18 hours at 536.49 hours, which represents a decrease in time of 108.70 hours, that is, 16.85% of the total. Likewise, the annual cost of a total of S /. 26,002.04 to S / 17,403.04 which also represents a decrease of S / 8,598.39, which is 33.07% of the total observed cost.